The Existence of Pancasila as a National Legal Identity in the Midst of Globalization - Joice Soraya; Shohib Muslim (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Pancasila, as the nation's foundation and source of all legal sources in Indonesia, plays a fundamental role in shaping the national legal identity. However, in the era of globalization, marked by the penetration of foreign legal values and liberalization across various sectors, the existence of Pancasila faces serious challenges both ideologically and normatively. This study aims to analyze how Pancasila remains relevant as the national legal identity in the face of globalization dynamics. The study employs a normative research approach using legal and philosophical frameworks. Data analysis is conducted qualitatively through a literature review of primary and secondary legal documents. The novelty of this research lies in its emphasis on the importance of repositioning the role of Pancasila not only as an ideological symbol but also as an operational principle in the formation and implementation of national law. The results of the study show that although globalization has an impact on the adaptation of the national legal system, the values of Pancasila can still serve as a solid foundation for the formulation of legal policies as long as there is a revitalization of understanding and institutional strengthening. The re-actualization of Pancasila values in national legal products has proven capable of filtering out global influences that are not in line with the character of the nation. This study recommends the need to strengthen Pancasila-based legal education, harmonize regulations with the noble values of the nation, and establish an ideological supervisory body to ensure that all laws and regulations are in line with Pancasila values as the national legal identity.